Effects of display curvature and task duration on proofreading performance, visual discomfort, visual fatigue, mental workload, and user satisfaction. (July 2019) - Park, Sungryul; Kyung, Gyouhyung; Choi, Donghee; Yi, Jihhyeon; Lee, Songil; Choi, Byeonghwa; Lee, Seungbae
Abstract: This study examined the effects of display curvature and task duration on proofreading performance, visual discomfort, visual fatigue, mental workload, and user satisfaction. Five 27″ rear-screen mock-ups with distinct curvature radii (600R, 1140R, 2000R, 4000R, and flat) were used. Ten individuals per display curvature completed a series of four 15 min comparison-proofreading trials at a 600 mm viewing distance. Only proofreading speed benefited from display curvature, with 600R providing the highest mean proofreading speed. Proofreading speed increased and accuracy decreased for all display curvatures over the 1 h proofreading period. Visual discomfort, visual fatigue, and mental workload increased during the first 15 min of proofreading. A decrease in critical fusion frequency during that period indicated increases in visual fatigue and mental workload. A short break between 15 min proofreading tasks could be considered to prevent further degradation of task performance and ocular health. Highlights: A display curvature radius equal to the viewing distance was beneficial. 600R is recommended for fast proofreading on a 27″ screen at a 600 mm distance. A break is needed after 15 min of proofreading for performance and visual discomfort.